Moving Times Mobility of the future - Weber, Julian (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2022)
Will we soon be driven by autonomous electric taxis rather than steering our own car? Should cities introduce car sharing? What role will electric scooters, cable cars or man-carrying drones play? This book finally explains understandably what buzzwords like e-mobility, autonomous driving, digitalization, and mobility as a service really mean, how far advanced these technologies are today, and above all how they mutually depend on each other. In addition to the technical aspects, also legislative and social trends are considered, which represent important framework conditions with decisive influence on the mobility of the future. From the contents - Mobility needs: Who wants to go where, when, and why - and how will this change? - Technological trends: e-mobility, digitalization, autonomous driving - what will the vehicles of the future be capable of? - Car sharing, ride-hailing, e-scooters or public transport: What are future alternatives to the private car? - Politics and society: How will the framework conditions for mobility develop in the future? - Mobility in transition: What should we do to prepare for the future? About the author For many years, Dr. Julian Weber headed BMW's e-mobility innovation incubator, where he is today responsible for the digital transformation through utilization of vehicle generated data. Since 2008, he has been an adjunct professor at the Department of Automotive Engineering at Clemson University (USA). This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation. .
Market, society and legislation in transition -- Demographic trends and infrastructure development -- Social trends in the environment of mobility -- Development of markets and customers -- Changing mobility needs -- Regulatory trends -- Technology trends -- Electric drives -- Autonomous driving -- Digitalisation -- Mobility as a service -- Car sharing and bike sharing -- Becoming dangerous: Ride Hailing, Ride Sharing -- Giving Back: Corporate Social Responsibility through Vehicle Fleets -- Scenarios for Tomorrow's Mobility.
Keywords: Sustainability; Transportation engineering; Traffic engineering; Automotive engineering; Electric power distribution; Sustainability; Transportation Technology and Traffic Engineering; Automotive Engineering; Energy Grids and Networks